Development of spontaneous motility in chick embryos supraspinal control - Sedlácek, J; Doskocil, M (Physiologia Bohemoslovaca, 1978)
Changes in spontaneous motility were studied in 11- to 19-day-old chick embryos after acute and chronic decapitation. Chronic decapitation was performed on the 2nd day of incubation, at stage 11--14. Up to the 15th day, acute decapitation merely reduced the frequency of spontaneous movements. In 17-day embryos it was followed by typical spinal shock, with transient complete disappearance of spontaneous movements of the embryo. The duration of spontaneous motor depression was proportional to the age of the embryo. After the 15th day of incubation, spinal decentralization changed continuous to discontinuous motor activity, with spontaneous paroxysms of high amplitude movements followed by long intervals of motor rest. Chronic decapitation was manifested, from the 15th day of incubation, in significant reduction of spontaneous movement frequency and again in discontinuous motility. A microscopic anatomical analysis of the spinal cord of decapitated embryos showed defects of the tracts in the lateral and ventromedial area of the cord and degenerative injury of the motoneurones in the ventral horns. Supraspinal control thus does not begin to act effectively on the spontaneous motility of chick embryos until about the 15th day of incubation. Supraspinal factors modulate both the frequency and the rhythm of spontaneous movements and are evidently also indispensable for normal morphological development of the spinal cord motor apparatus of chick embryos.
Keywords: kuřecí embryo; Animals; mícha; Time Factors; Movement; Spinal Cord; časové faktory; pohyb; Chick Embryo; Motor Neurons; zvířata; motorické neurony